ANALISIS EKONOMI RUMAH TANGGA NELAYAN MINI PURSE SEINE DI KECAMATAN BONTOBAHARI KABUPATEN BULUKUMBA - Sitti Fakhriyyah; M. Chasyim Hasani; Asnia Astuti (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
This study aims to determine the big production, an endless hours of work, income levels and household allocation mini purse seine fishing in the District Bontobahari, Bulukumba. The data collection was conducted in February-March 2016. The location determination is done purposively with consideration that fishermen in the area generally work as fishermen using mini purse seine fishing gear. This is a descriptive study using a mixture  method. A mixed method research approach that combines or links between a descriptive method qualitative and quantitative. Descriptive research is a problem-solving process was investigated by describing the state of the object of research at the present time based on the facts that appear on the site. Qualitative methods are methods that form of words, sentences, schematics and drawings. Quantitative method is a method in the form of numbers, charts and graphs. The sampling method used in this study is a cluster random sampling, namely fishermen grouped by strata that retainer and mustard. The results showed domestic production of 5.43 tons fishermen, the outpouring of fishermen working hours allows for the alternative job search to fill the time, comparison of income retainer with the crew very much which is about 87.71%:12.29%. ABK fishermen as well as food expenditure more than non-food.Keywords: Outpouring of Work, Mini Purse Seine, Income, Household Fishermen